Relationship between occurrence of lahar and hydraulic properties of ashfall covered ground in the Arimura River basin of Sakurajima Volcano, Japan - Sugawara, Hayato; Gonda, Yutaka (Journal of the Civil Engineering Forum, 2025)
When volcanic ash accumulates on the surface layer of slopes, it decreases the hydraulic conductivity of the ground, which can trigger lahars even due to small rainfall. Understanding the impact of changes in surface conditions on lahar occurrence is crucial for disaster prevention. This study employed a runoff analysis model based on the kinematic wave method to evaluate the surface conditions indirectly by hydraulic conductivity parameter values at the time of lahar occurrence. This study tried to reveal the relationship between the change of hydraulic conductivity parameter values in each lahar event and observed monthly ashfall data. The study area is the Arimura River basin in Sakurajima, Japan. Sakurajima volcano is still active today (2025), and new fresh volcanic ash is depositing on the surface ground. As a result, the model can find the optimal parameter in 41 out of 55 lahar events that occurred in the Arimura River basin on Sakurajima between 2015 and 2020. Next, we examined the characteristics of lahar events that could not be reproduced by our runoff analysis model. As a result, we found that lahars which occur after a lot of volcanic ashfall or contain large boulders have bad reproducibility. Next, we analyzed the relationship between the optimal parameter values for the 41 events and the monthly observed ashfall data. The results indicated a trend in which the optimal parameters decrease under conditions of increasing monthly ashfall, and the coefficient of determination was approximately 0.18. When considering the effect of preceding rainfall prior to lahar, a visual tendency was observed for the hydraulic conductivity parameter values to decrease with increasing preceding rainfall.